Avaliação de indicadores do estresse oxidativo e da atividade da enzima acetilcolinesterase sangüínea em pacientes com diagnóstico de acidente vascular cerebral isquêmico - Corrêa, Maísa de Carvalho (2006)
In ischemic stroke, damage to the brain is caused by a reduction or complete blockage of blood flow to parts of the brain, resulting in glucose and oxygen deficiency. It is a leading cause of mortality and disability particularly in the elderly. The majority of strokes are not fatal and survivors are at a high risk of subsequent vascular complications and new vascular accidents. Hypertension is the most important risk factor in strokes, being that it is present in 70% of all cases. Oxidative stress is believed to be one of the mechanisms taking part in neuronal damage in stroke. The key role the cholinergic system plays in normal brain functions and in memory disturbances of several pathological processes, such as in cerebral blood flow regulation, has been well documented. This study investigated the oxidative status and acetylcholinesterase (AChE) activity in whole blood in patients diagnosed with the acute and chronic stage of ischemia, as well as with hypertension. We determined the catalase activity in the blood, reduced glutathione (GSH) in erythrocytes, and TBARS and protein carbonyl content from serum samples. The oxidative profile of lipids and proteins represented by MDA levels and protein carbonylation content, respectively, showed increased levels both in the acute ischemic group and in the hypertensive group, when compared to the control. Catalase activity and GSH levels in the acute group also were higher than in the hypertensive and control groups. No difference was found between the catalase activity of the chronic ischemic group and the hypertensive group (p< 0.05). The activity of AChE in acute ischemic patients was significantly higher than that presented by the control, hypertensive and chronic ischemic patients (p<0.05). No significant difference was observed between the chronic and control groups. The hypertensive group presented AChE activity significantly lower than the other groups. The results suggest increased antioxidant defense as a compensatory mechanism in consequence of the overproduction of reactive oxygen species (ROS) after acute stroke. This sudy also demonstrated that hypertension, in and of itself, acts as a prevalent risk factor of stroke, contributing to oxidative cellular damage. Futhermore, the results revealed that ischemia exerted a modulator effect on AChE activity in erythrocytes, in an attempt to maintain adequate levels of the neurotransmitter acetylcholine (ACh), as a response to the differents phases following neurological injury caused by ischemia. The ischemic event, in spite of having a defined location, results in a systemic disorder that induces changes, which can be detect by mesuring the peripheral markers of oxidative stress and AChE activity in erytrocytes.